A Glucose Biosensor Based on Direct Electron Transfer of Glucose Oxidase on PEDOT Modified Microelectrode. Issue 6 (19th March 2020) - Chen, Junhao; Zheng, Xiaoyuan; Li, Yulin; Zheng, Haitao; Liu, Yanjun; Suye, Shin-ichiro
Abstract : Implantable glucose biosensor based on poly (3, 4-ethylenedioxythiophene) (PEDOT) modified carbon fiber (CF) microelectrode was fabricated for the first time. Main appeal of this work was the immobilization of glucose oxidase (GOx) on PEDOT film by electrostatic interaction, which resulted in the direct electron transfer (DET) between the active sites of enzyme and electrode in the help of PEDOT. The sensor exhibited selective response to glucose in the presence of some common interference. The biosensor operates at a low potential of −0.65 V vs Ag/AgCl, and the amperometric response was linear over range from 0.5 mM to 15 mM for glucose with a sensitivity of 8.5 μ A·cm −2 ·mM −1 . The Michaelis-Menten constant was calculated as 6.5 mM, and the sensor retain 81.3% sensitivity after 60 d storage. Moreover, the extremely simple process of DET construction could be potentially extended for the mass production.